Slicepedia: Towards Long-Tail Resource Production through Open Corpus Reuse - LAWLESS, SEAMUS (Springer, 2012)
The production of resources supporting the needs of Adaptive Hypermedia Systems (AHS) is labor-intensive. As a result, content production is focused upon meeting the needs of resources with higher demand, which limits the extent upon which long tail content requirement niches of AHS can be met. Open corpus slicing attempts to convert the wealth of information available on the World Wide Web, into customizable information objects. This approach could provide the basis of an open corpus supply service meeting long tail content requirements of AHS. This paper takes a case study approach, focusing on an educational sector of adaptive hypermedia, to test out the e?ect of using Slicepedia, a service which enables the discovery, reuse and customization of open corpus resources. An architecture and implementation of the system is presented along with a user-trial evaluation suggesting slicing techniques could represent a valid candidate for long tail content production supply of AHS.
Lecture Notes in Computer Science
The 11th International Conference on Web-based Learning, ICWL 2012
PUBLISHED
Sinaia, Romania
Keywords: Adaptive Hypermedia; Slicing